(untitled) (International Journal of Engineering and Computer Science, 2017)
: Image processing based student attendance System is the easiest way to keep track of attendance for organizations such as Educational Institutions, Business organizations. Among the person identification methods, face recognition is known to be the most natural ones; since the face modality is the modality that uses to identify people in everyday lives. Although other methods, such as fingerprint identification can provide better performance, but they are not appropriate for natural smart interactions due to their intrusive nature. This face detection differentiates faces from non faces and is therefore essential for accurate attendance [6]. Our Proposed strategy involves face recognition for marking the student attendance. Raspberry pi is used for face detection and face recognition. The camera will be connected to the raspberry pi module. The student database is collected. The database includes name of the students with their registered numbers and their face images. Camera will be placed in front of the class in such a way that it can capture the entire class, which is connected to the raspberry pi. Thus with the help of this system time will be saved and it is so convenient to record the attendance at any time throughout the day.